Histology of the tracheolar insect retina system - PESSACQ, TOMÁS P. (Revista Colombiana de Entomología, 1999)
Histology and architectonics of the tracheolar system in the retina of insects are studied. It is concluded that the tracheolar network is denser at the level of the external chiasma. The topography of tracheae in the external ganglion layer is also briefly described.